2014
DOI: 10.1177/0963721414549750
|View full text |Cite
|
Sign up to set email alerts
|

Does Lower Cognitive Ability Predict Greater Prejudice?

Abstract: Early empirical evidence (Adorno et al., 1950) Abstract Historically, leading scholars proposed a theoretical negative association between cognitive abilities and prejudice. Until recently, however, the field has been relatively silent on this topic, citing concerns with potential confounds (e.g., education levels). Instead, researchers focused on other individual-difference predictors of prejudice, including cognitive style, personality, negativity bias, and threat. Yet there exists a solid empirical paper t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 39 publications
(78 reference statements)
4
73
0
1
Order By: Relevance
“…Applied to the relationship between RWA and perceived external threat, people higher in RWA tend to seek confirmation and justification for their beliefs and look for signs that their surrounding external world is indeed dangerous and threatening. Such a bidirectional path seems much less likely in the case of NFC, where there is a broad consensus that dispositional epistemic needs lie at the basis of socio-ideological attitudes such as RWA (see e.g., Dhont & Hodson, 2014;Jost et al, 2003;Roets & Van Hiel, 2011a;. Exactly because of the lack of a theoretical rationale for the reverse path, we did not include a measure of NFC in the second wave of data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Applied to the relationship between RWA and perceived external threat, people higher in RWA tend to seek confirmation and justification for their beliefs and look for signs that their surrounding external world is indeed dangerous and threatening. Such a bidirectional path seems much less likely in the case of NFC, where there is a broad consensus that dispositional epistemic needs lie at the basis of socio-ideological attitudes such as RWA (see e.g., Dhont & Hodson, 2014;Jost et al, 2003;Roets & Van Hiel, 2011a;. Exactly because of the lack of a theoretical rationale for the reverse path, we did not include a measure of NFC in the second wave of data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Moutafi et al (2004Moutafi et al ( , p. 1015 proposed that people with lower intelligence "become more conscientious in order to cope with their disadvantage" or that "more intelligent individuals do not become so conscientious, as they can rely on their fluid intelligence to accomplish most tasks". Research has also found that lower cognitive abilities predict higher RWA scores (Deary, Batty, & Gale, 2008;Heaven, Ciarrochi, & Leeson, 2011), higher levels of conservatism (Hodson & Busseri, 2012;Stankov, 2009) and greater prejudice (Dhont & Hodson, 2014). The latter is of some relevance as there is evidence that individuals who identified more with their nation tended to express greater prejudice against non-nationals (Tajfel & Turner, 1979).…”
Section: Numeracymentioning
confidence: 97%
“…A reanalysis by Hodson and Busseri (2012) specifically focusing on racial prejudice confirmed that, in two large-scale datasets (Ns > 7000), lower generalised THE PERSON-BASED NATURE OF PREJUDICE 15 intelligence in childhood predicts increased adult racism in both men and women, even after statistically controlling for educational level and socioeconomic status (SES). Given that the prejudice measures in such studies are explicit, and that social norms regarding prejudice are also explicit and do not require sophistication for people to follow them, it is unlikely that such findings are due to differences in social desirability concerns between those lower vs. higher in cognitive abilities (see Dhont & Hodson, 2014a;Hodson & Busseri, 2012). These relations are also robust: A recent meta-analysis investigating the association of cognitive ability with right-wing ideological attitudes and prejudice (Onraet et al, 2015) revealed an average effect size of −.28 for studies on generalised prejudice (see our Table 2).…”
Section: Cognitive Abilitiesmentioning
confidence: 99%
“…Relatedly, Wilson (1973) operationalised conservatism as "a generalized susceptibility to experiencing threat or anxiety in the face of uncertainty" (p. 259). As such, those higher in conservatism, particularly social or cultural (vs. economic) conservatism, 2 are predisposed towards prejudicial orientations regarding lower status outgroups (see Cornelis & Van Hiel, 2006;Dhont & Hodson, 2014a;Hodson, 2014). Cast in contemporary terms, the "core ideology of conservatism stresses resistance to change and justification [or acceptance] of inequality" (Jost, Glaser, Kruglanski, & Sulloway, 2003, p. 339).…”
Section: Conservatismmentioning
confidence: 99%
See 1 more Smart Citation